“Estrategias Metodológicas y Necesidades Educativas Especiales en estudiantes con Discapacidad Intelectual de la Unidad Educativa Especializada “Carlos Garbay”.Riobamba. 2015-2016”. - Naspud Villafuerte, Ana Gabriela (2017)
This research is about the Methodological Strategies and Special Educational Needs Students with Intellectual Disability in a institution of Special Educational Unit "Carlos Garbay". Riobamba. Period 2015-2016,” which intention is to investigate the tactics used by teachers to attend the special educational needs of students. Therefore this study is justified by the contribution that we make in offering practical orientations that allow developing abilities and potentialities in the students. The objective of this research was to determine the methodological strategies used by teachers to act in response to the Special Educational Needs of students with Intellectual Disabilities. Since the methodological point of view it was a non-experimental, exploratory, field and documentary study. by means of the time was transversal, the population was composed of 44 students; 30 men, 14 women and 20 teachers, the technique used was the survey, with its instrument the questionnaire. The conclusions allow us to confirm that the main Methodological Strategies used by teachers are active techniques such as motivation activities, previous knowledge, reinforcement activities, specific exercises to expand care; That students with Special Educational Needs present in general the following characteristics: difficulty in the area of communication, decreased cognitive abilities, slower learning pace, usually present problems in the affective area; That the way in which the strategies used by the teachers respond to the N.E.E. Guarantees the students' learning, allowing them to provide an educational response according to their needs, with regard to their rhythm and style of learning.